2022
DOI: 10.1177/00219096211069641
|View full text |Cite
|
Sign up to set email alerts
|

The Covid-19 Pandemic: Limited Water Access and the Precarity of Women Fishers at Lake Kariba, Zimbabwe

Abstract: Man-made reservoirs are constructed to meet certain purposes and Lake Kariba, Zimbabwe, was designed for hydroelectric power generation. However, it has developed other multiple uses, and the growth of fisheries on the lake has had a significant impact on the livelihoods of local communities. The declaration of Covid-19 as a pandemic in Zimbabwe in March 2020 was quickly followed by the imposition of national lockdowns with varying levels of severity up to the present day. This was done to curtail the spread o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Though some joined the fishing activity at Lake Kariba, its sustainability was also impacted by the pandemic and lockdowns. It has been reported that national parks officials harassed and confiscated people’s fishing gear during the lockdowns (Nhiwatiwa and Matanzima, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Though some joined the fishing activity at Lake Kariba, its sustainability was also impacted by the pandemic and lockdowns. It has been reported that national parks officials harassed and confiscated people’s fishing gear during the lockdowns (Nhiwatiwa and Matanzima, 2022).…”
Section: Findings and Discussionmentioning
confidence: 99%
“…For example, during the 1980s and 1990s, précarité in France became widely conceived both in academic and political discourse as extending beyond the sphere of work and into the general precariousness of life (Adams and Darby, 2020; see also Butler, 2013). The precarity concept has further been applied in different fields of study such as development-induced displacement and resettlement (Matanzima, 2021; Wilmsen and Adjartey, 2020), urban and rural livelihoods (Gukurume, 2018; Nhiwatiwa and Matanzima, 2022) and (im)mobility and migration (Banki, 2013; Martin et al, 2019). Constituted by extreme flexibility, impermanence and insecurity, it is seen to be the cause of a series of psychosocial pathologies in contemporary society, such as heightened anxiety about one’s future (Dines, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Poverty can be classified as one of the key issues in rural areas, therefore, the marketing of horti-tourism could create entrepreneurship opportunities, employment creation and income generation for the farmers and other people living within the community due to domestic and international tourist arrivals. In turn, this can curtail the unemployment issues bedevilling rural communities within emerging countries (Nhiwatiwa and Matanzima, 2022).…”
Section: Horti-tourism In Literaturementioning
confidence: 99%
“…Te surface water temperature data for Lake Kariba were provided by the University of Zimbabwe Lake Kariba Research Station (UZLKRS), and the data were collected at Station 7, Sanyati mouth, 1st cross, Gachegache mouth, Charara, Nyaodza, and Nyenje for the period July 2014 to December 2017 [25].…”
Section: Data Collectionmentioning
confidence: 99%